HUBUNGAN DURASI KOLESISTEKTOMI LAPAROSKOPI DENGAN PERUBAHAN KADAR BILIRUBIN TOTAL PASIEN KOLELITIASIS - Manik, Sarmono Lotma Saipon; Wibowo, Agung Ary; Yuliana, Ida; Winata, Winardi Budi; Rosida, Azma (Homeostasis, 2024)
Abstract: Laparoscopic cholecystectomy is the gold standard treatment for treating symptomatic cholelithiasis. Recent studies have shown an increase in total bilirubin levels in patients undergoing laparoscopic cholecystectomy due to liver ischemia caused by CO2 pneumoperitoneum during the procedure. The duration of cholecystectomy is thought to be related to changes in total bilirubin levels that occur, where the longer the duration, the longer the ischemia that occurs so that total bilirubin levels will increase. This study aims to analyze the correlation between the duration of laparoscopic cholecystectomy and changes in total bilirubin levels in cholelithiasis patients at RSUD Ulin Banjarmasin. This study uses an analytical observational method with a cohort study approach. There is a positive significant correlation between the duration of laparoscopic cholecystectomy and changes in total bilirubin levels in cholelithiasis patients at RSUD Ulin Banjarmasin with moderate strength (p = 0.000; r = 0.511). Keywords: cholelithiasis, laparoscopic cholecystectomy, total bilirubin. Abstrak: Kolesistektomi laparoskopi adalah tatalaksana baku emas untuk mengobati kolelitiasis bergejala. Studi terkini menunjukkan terjadinya peningkatan kadar bilirubin total pada pasien yang menjalani kolesistektomi laparoskopi karena iskemia hati yang disebabkan pneumoperitoneum CO2 selama prosedur. Durasi kolesistektomi diduga berhubungan dengan perubahan kadar bilirubin total yang terjadi dimana semakin lama durasinya maka semakin lama iskemia yang terjadi sehingga kadar bilirubin total akan semakin meningkat. Penelitian ini bertujuan untuk menganalisis hubungan durasi kolesistektomi laparoskopi dengan perubahan kadar bilirubin total pasien kolelitiasis di RSUD Ulin Banjarmasin. Penelitian ini menggunakan metode observasional analitik dengan pendekatan studi kohort. Terdapat hubungan bermakna positif antara durasi kolesistektomi laparoskopi dengan perubahan kadar bilirubin total pasien kolelitiasis di RSUD Ulin Banjarmasin dengan kekuatan sedang (p = 0,000; r = 0,511). Kata-kata kunci: kolelitiasis, kolesistektomi laparoskopi, bilirubin total.